Identification of PSORS1C3 variants in Vietnamese patients with psoriasis disease - Liên, Nguyễn Thị Kim; Việt, Lê Bắc; Kỳ, Lê Đình; Biển, Nguyễn Văn; Bền, Nguyễn Văn; Hoàng, Nguyễn Huy (Vietnam Journal of Biotechnology, 2018)
Psoriasis is an immune disorder disease which has genetic cause. It is benign disease, and usually lies in dormant status in the body until the patient triggered by a variety of factors such as environment, lifestyle and diet. The disease has an effect on the aesthetic, many serious complications and affects a large number of the world population. Until now, there are no specific method of cure only treatment of disease stabilization, avoidance complications and improvement quality of life for patients. Genetic studies of psoriasis have been identified 13 loci associated to susceptibility of disease. Among them, the PSORS1 region on chromosome 6p21.3 was identified as highest relevant to susceptibility of disease. In this study, blood samples of the Vietnamese patients with psoriasis disease were collected and investigated. Exons in PSORS1C3 gene, one gene in locus PSORS1, in psoriasis patients were amplified by using specific primer pairs. The single nucleotide polymorphisms (SNP) of PSORS1C3 gene were determined by sequencing and comparing with the reference sequence in Ensembl. We found out 14 SNPs including of 6 SNPs rs3868542, rs11507945, rs11507946, rs3871247, rs11507947, rs3871246 on exon 1; 2 SNPs rs3099189, rs3132517 on exon 2; 6 SNPs rs887467, rs887468, rs1061503, rs2269711, rs11507948 and rs11507949 on exon 3 of PSORS1C3 gene in Vietnamese patients with psorisis disease. The results showed that there was one SNP rs3871246 have significant association to susceptibility of disease with p